The Relationship Between Knowledge And Attitudes Of Pregnant Women With Behaviors To Prevent Malari Complications In Pregnancy - Muji Lestari; Yeni Wardhani; Winda Lestari Pauta (Journal of Midwifery Science: Basic and Applied Research, 2022)
Malaria in pregnancy can be caused by various types of Plasmodium malaria and Plasmodium falciparum is a plasmodium that has a bad impact that can increase maternal morbidity and mortality and has a bad impact on babies in the womb. In pregnant women, malaria can cause complications of anemia, cerebral malaria, pulmonary edema, kidney failure and can cause death. In the fetus it causes abortion, premature delivery, low birth weight, and fetal death. This research method uses descriptive with cross sectional research design. The study sample was 53 pregnant women who underwent Antenatal Care examinations at the Koya Barat Health Center in 2021. The sampling method used the Accidental Sampling technique. The results showed that the majority of respondents aged 20-35 years were 48 people (90.6%). Most of respondents' education is SMA 28 (52.8%). Good knowledge of 16 respondents (30.2%) and poor knowledge of 37 respondents (69.8%). Positive attitude of respondents as many as 19 respondents (35.8%) and negative attitudes of 34 respondents (64.2%). The behavior of the respondents is sufficient as many as 36 respondents (67.9%) and the behavior of the respondents is less as many as 17 respondents (32.1%). Conclusion There is a significant relationship between knowledge of pregnant women and the behavior of preventing malaria complications in pregnancy with a p-value of 0.045. There is no significant relationship between attitude and prevention of malaria complications in pregnancy with a p value of 0.502 at the Koya Barat Health Center. Efforts to prevent malaria must continue to be carried out in risk groups, namely pregnant women, in order to reduce the number of malaria cases and reduce maternal and infant mortality.